2016
DOI: 10.1051/0004-6361/201628666
|View full text |Cite
|
Sign up to set email alerts
|

Near-Earth asteroid (3200) Phaethon: Characterization of its orbit, spin state, and thermophysical parameters

Abstract: Context. The near-Earth asteroid (3200) Phaethon is an intriguing object: its perihelion is at only 0.14 au and is associated with the Geminid meteor stream. Aims. We aim to use all available disk-integrated optical data to derive a reliable convex shape model of Phaethon. By interpreting the available space-and ground-based thermal infrared data and Spitzer spectra using a thermophysical model, we also aim to further constrain its size, thermal inertia, and visible geometric albedo. Methods. We applied the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
110
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 63 publications
22
110
3
Order By: Relevance
“…This is because the approximate plane containing the preferred and alternate pole solutions is roughly perpendicular to our line-of-sight during the asteroid's close approach, and so an Earth-bound observer's sub-latitude crosses Phaethon's equator at about the same time in either case (e.g. 13 hours later for the Hanuš et al (2016) alternate pole solution). As a result, our finding of a color difference with sub-latitude would still stand, but the exact distribution on the asteroid's surface would be different.…”
Section: Surface Variationsmentioning
confidence: 98%
See 2 more Smart Citations
“…This is because the approximate plane containing the preferred and alternate pole solutions is roughly perpendicular to our line-of-sight during the asteroid's close approach, and so an Earth-bound observer's sub-latitude crosses Phaethon's equator at about the same time in either case (e.g. 13 hours later for the Hanuš et al (2016) alternate pole solution). As a result, our finding of a color difference with sub-latitude would still stand, but the exact distribution on the asteroid's surface would be different.…”
Section: Surface Variationsmentioning
confidence: 98%
“…Ohtsuka et al (2009) andAnsdell et al (2014) found that the northern latitudes of Phaethon would be preferentially heated and bluer in B-V, using the pole solution of Krugly et al (2002). However, Hanuš et al (2016) argued, using an updated pole solution, that Phaethon has not suffered preferential heating over the last thousands of years.…”
Section: Surface Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we adopt the initial orbital elements of nominal orbit and their uncertainties for EV5 from the Minor Planet Center (MPC)(see Table 3). Similar to Hanuš et al (2016), we generated 1000 orbital clones except for the nominal orbit. All the orbital elements in each clone was yielded within the uncertainties given in Table 3.…”
Section: Simulations Of Dynamical Historymentioning
confidence: 99%
“…NEATM is by necessity a simple approximation of the real thermal behavior of asteroid surfaces; more detailed thermophysical modeling (e.g. , Spencer 1990;Lagerros 1997;Wright 2007;Alí-Lagoa et al 2014;Koren et al 2015;Hanuš et al 2016;Nugent et al 2017) can provide improved constraints on the physical and thermal properties of an asteroid if multiple viewing geometries are available, though at the expense of greatly increased computation time. We provide NEATMderived physical properties here as a springboard for more detailed modeling of targets of interest.…”
Section: Neatmmentioning
confidence: 99%